Preparation of a Ni–Fe-based transition metal phosphide as an efficient electrocatalyst for the oxygen evolution reaction. Issue 19 (7th September 2022) - Tang, Huanhuan; Qi, Yufan; Feng, Danning; Chen, Yangyang; Liu, Liying; Hao, Lei; Yue, Kefen; Li, Dongsheng; Wang, Yaoyu
Abstract : Ni2 P–Fe2 P/NF is produced by phosphating MOF derivatives and presents excellent OER performance (222 mV at 100 mA cm −2 ). Abstract : It is incredibly essential to generate catalysts that both have abundant reserves and are highly active for the oxygen evolution process (OER) in electrocatalytic water-splitting technology. Prussian blue analogs (PBAs) offer enormous potential in the field of the OER due to their programmable metal centers, controllable electron density and customizable structure. The active components of the Ni–Fe PBA nanocubes were deposited on the Ni(OH)2 nanoflower structures to create distinct morphologies. After phosphidation at 375 °C with CN group decomposition in Ni–Fe PBA, the obtained bimetallic phosphide demonstrated excellent oxygen evolution reaction (OER) activity in alkaline solutions, reaching current densities of 100 and 200 mA cm −2 with overpotentials of only 222 and 242 mV, respectively. The Tafel slope is only 40.9 mV dec −1 . Furthermore, the Ni2 P–Fe2 P/NF catalyst shows long-term stability without noticeable deterioration after 100 hours. Our research identifies a highly effective technique for creating enhanced electrode materials for OER electrocatalysts.